Global series: Complex regional pain syndrome: abstracts from the International Association for the Study of Pain complex regional pain syndrome SIG virtual symposia 2021. (16th January 2023) - Lewis, Jennifer S.; Kashif, Muhammad; Maan, Aasam; Ciampi de Andrade, Daniel; Casey, Michelle; Moon, Jee Youn; Lin, Chih-Peng; Danielsson, Lena; Quek, Terence; Díez Tafur, Rodrigo; Aloweidi, Abdelkarim; Birklein, Frank; et al.
Abstract : The aim of this IASP complex regional pain syndrome (CRPS) SIG Global Series 2021 was to bring together clinicians including those from developing countries to better understand the clinical presentation of complex regional pain syndrome in countries with less well-published patient populations. The purpose was to learn from each other about the range of treatments, successful outcomes, and challenges experienced. These meeting proceedings comprise abstracts from nine countries that span 4 continents and are summaries of online presentations delivered by speakers representing these countries over the course of 2 symposia. The symposia were attended by a global audience of approximately 360 people. Patients with CRPS were described and treated by clinicians from countries across Asia (Pakistan, Jordan, South Korea, Taiwan, and Singapore), South America (Brazil and Peru), Africa (South Africa), and Europe (Norway). This reflects that CRPS exists across borders, ethnicities, and cultures. These proceedings provide a broader perspective within the international pain community about how we can better understand and treat CRPS across the globe.